African Latin in Early Modern Thought: Language, Race, and Philology - Vozar, Thomas Matthew (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
This article takes John Milton’s description of the “knotty Africanisms” of the Church Fathers as the launching point for an investigation of African Latin in early modern thought. The first part traces the development of a conception of Africitas or Africanismus as a peculiarly African form of Latin in Western scholarship from Erasmus to the early eighteenth century. The second part considers early modern African Latinists such as the Granada professor Juan Latino and the Jamaican poet Francis Williams and their reception in this light. The concept of Africitas is shown to have taken hold at the same time as the globalization of Latin.